The implementation of single-judge trials at the Lumajang religious court from the perspective of Soerjono Soekanto’s legal effectiveness theory (Based on supreme court decision no. 215/KMA/HK2.6/XI/2024) - Aminatol Munauwarah; Syabbul Bachri (Privietlab, 2025)
This study examines the implementation of single-judge hearings at the Religious Court of Lumajang based on Chief Justice’s Decree Number 215/KMA/HK2.6/XI/2024. This policy was introduced as a strategic response to the increasing number of cases that exceeded the available number of judges. Through this mechanism, the judicial process is expected to operate more efficiently while upholding the principles of fast, simple, and low-cost justice. This study employs an empirical legal method using a qualitative approach. Data were collected through direct observations, interviews with judges and court officers, and the analysis of official documents. This approach enables a comprehensive understanding of how the policy is implemented in practice and provides an objective assessment of its effectiveness. The findings demonstrate that the single-judge system has been implemented effectively, according to Soerjono Soekanto’s theory of legal effectiveness. The policy fulfills five determining factors: clear legal substance, competent law enforcers, adequate facilities, community acceptance, and an adaptive legal culture. These components collectively support the smooth execution of this system. Overall, the single-judge mechanism contributes significantly to improving judicial performance at the Lumajang Religious Court. This accelerates case resolution and strengthens public trust in the judiciary. Thus, this system represents an important step in the broader reform of Indonesia’s religious-court system.